Differences in body image, self-esteem, and response to teasing based on gender - Horne, Jacqueline (2005)
The current study investigated the differences in body image, self-esteem,and response to teasing based on gender in a predominantly African American sample. Participants included 50 college age students from South Carolina State University. Participants were group administered a demographics information sheet, the Multidimensional Body Self-Relation Questionnaire-Appearance Scale(MBSRQ-AS; Cash, 2000), the Multidimensional Self Esteem Inventory (MSEI;O'Brien & Epstein, 1988), a Negative Verbal Commentary Scenario, and the Physical Appearance Related Teasing Scale (PARTS; Thompson, Fabian,Moulton, Dunn, & Altabe, 1991). Three separate Multivariate Analysis of Variance (MANOVAs) was conducted. Results indicated no significant difference on the Appearance Evaluation and Appearance Orientation Scales. However,there was a significant difference for the Body Areas Satisfaction and Overweight Preoccupation Scale, with the males scoring higher than females. Also there was a significant difference on the Self-Classified Weight Scales, with females scoring higher than males. The results indicated that the females scored higher than the males on the Global Self Esteem Scale, Competence, Personal Power, Body Appearance, Body Functioning, and Identity Formation. Females scored lower than males on Defensive Self-enhancement. There were no Significant differences found on measures of the impact of teasing. Exploratory analyses,limitations, and implications for future research will be discussed in the paper.